Digital Distance Learning and the Transformation of Vocational Schools From a Qualitative Perspective - Delcker, Jan; Ifenthaler, Dirk (Frontiers in Education, 2022)
Digital distance learning has become one of the main modes of education at vocational schools during the COVID-19 pandemic. A large-scale survey with almost 4000 stakeholders from 15 vocational schools in Germany was conducted to analyze the current state of digital distance learning, with the goal to identify the challenges teachers, students, school leaders, parents and training companies face when digital distance learning processes are implemented. A total of N = 1493 qualitative statements have been analyzed as part of the survey. The results of the qualitative analysis suggest the influence of digital distance learning on eight categories within school development, namely teaching, feedback, organization, collaboration, personal resources, technical infrastructure, perceived learner success and professionalization. The identification of challenges within these categories can help school leaders at vocational schools and policy makers to transform the experiences during the ad-hoc implementation of digital distance practices into sustainable school development processes. The research work also proposes a transformation of existing theoretical frameworks of school development in the light of digitalization.